1996
DOI: 10.1074/jbc.271.15.8605
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relations of Smooth Muscle Calponin

Abstract: Calponin has been implicated in the regulation of smooth muscle contraction through its interaction with F-actin and inhibition of the actin-activated MgATPase activity of phosphorylated myosin. Both properties are lost following phosphorylation (primarily at serine 175) by protein kinase C or calmodulin-dependent protein kinase II. To evaluate further the functional importance of serine 175, wild-type calponin and three site-specific mutants (S175A, S175D, and S175T) were expressed in Escherichia coli and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Caldesmon undergoes phosphorylation during the contractile activation of tracheal smooth muscle [144]; thus this could provide a thin-filament mediated mechanism for the regulation of actomyosin ATPase activity that would operate independently of MLC phosphorylation. Calponin has also been found to inhibit actomyosin ATPase activity and actin sliding velocity in vitro [97,145], and the inhibition of actomyosin ATPase activity by calponin can be reversed by phosphorylation [106,145,146]. Contractile activation with carbachol induces a transient increase in calponin phosphorylation in tracheal smooth muscle [97,145].…”
Section: Molecular Basis For the Mechanical Properties Of Tracheal Smmentioning
confidence: 99%
“…Caldesmon undergoes phosphorylation during the contractile activation of tracheal smooth muscle [144]; thus this could provide a thin-filament mediated mechanism for the regulation of actomyosin ATPase activity that would operate independently of MLC phosphorylation. Calponin has also been found to inhibit actomyosin ATPase activity and actin sliding velocity in vitro [97,145], and the inhibition of actomyosin ATPase activity by calponin can be reversed by phosphorylation [106,145,146]. Contractile activation with carbachol induces a transient increase in calponin phosphorylation in tracheal smooth muscle [97,145].…”
Section: Molecular Basis For the Mechanical Properties Of Tracheal Smmentioning
confidence: 99%
“…Reactions containing Ca# + were made 10 mM in EDTA at the end of the reaction. Data from our previous studies have demonstrated that similar reactions under identical experimental conditions produced effective phosphorylation of calponin at serine-175 [33].…”
Section: In Vitro Phosphorylation Of Calponinmentioning
confidence: 85%
“…Furthermore, the presence of certain submolecular structures unaffected by the modification of serine-175 in both free and thin filament-associated calponins indicates that the serine-175 phosphorylation-based conformational modulation is a set of targeted allosteric effects. Although the S175A substitution eliminated this primary PKC phosphorylation site [33], and is not a natural regulatory mechanism for calponin structure and function, the change of calponin conformation due to the alanine mutation supports the critical role of serine-175 in determining calponin molecular conformation and functional state. These data also provide evidence that an alanine mutation is not a ' silent ' substitution, and should be applied with caution in mutagenesis mapping of protein structure-function relationships.…”
Section: Antibody Epitope Analysis To Monitor Calponin Conformationalmentioning
confidence: 90%
See 2 more Smart Citations